2018
DOI: 10.1186/s13014-018-1084-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfractionated abdominal reirradiation for gastrointestinal malignancies

Abstract: BackgroundWe sought to determine the role of abdominal reirradiation for patients presenting with recurrent or new primary gastrointestinal (GI) malignancies. At our institution, we have established a hyperfractionated, accelerated reirradiation regimen consisting of 39 Gray (Gy) in 26 twice-daily fractions. Although this regimen is used frequently in the pelvis, we sought to determine its toxicity and efficacy for abdominal tumors.MethodsTwenty-four patients who received abdominal reirradiation with a hyperfr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Because of the exceptional OAR sparing uniquely achieved with an MR-Linac we used a dose escalation strategy for most patients; nearly all were prescribed >40 Gy EDQ2 10 and nearly half >50 Gy EDQ2 10. Our use of higher prescription doses was motivated by data suggesting that this can improve long-term treatment efficacy (4,5,17,18). Koom et al reported significantly higher LC among locally recurrent rectal cancer patients prescribed >50 Gy EQD2 10 who did not have subsequent surgery (5).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because of the exceptional OAR sparing uniquely achieved with an MR-Linac we used a dose escalation strategy for most patients; nearly all were prescribed >40 Gy EDQ2 10 and nearly half >50 Gy EDQ2 10. Our use of higher prescription doses was motivated by data suggesting that this can improve long-term treatment efficacy (4,5,17,18). Koom et al reported significantly higher LC among locally recurrent rectal cancer patients prescribed >50 Gy EQD2 10 who did not have subsequent surgery (5).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, reRT has been prescribed to 30 to 40 Gy EQD2 10 to minimize the risk of severe toxic effects, although these modest doses are not associated with durable LC, especially in patients who do not proceed to surgery. 4 Owing to the exceptional OAR sparing uniquely achieved with an MR-Linac, we used a dose escalation strategy for most patients; nearly all were prescribed ≥40 Gy EDQ2 10 , and nearly half were prescribed ≥50 Gy EDQ2 10. Our use of higher prescription doses was motivated by data suggesting that this can improve long-term treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations